Assessing the Distinct Factors Driving Violent, Drug and Disorder-Related Prison Misconduct from Longitudinal Data in Northern Ireland. (28th September 2021) - Butler, Michelle; McNamee, Catherine B; Kelly, Dominic
Abstract: Studies are increasingly interested in how different categories of prison misconduct may affect reoffending. Yet few studies investigate the distinct factors driving different types of misconduct and those that do are often cross-sectional or retrospective. This study uses a prospective longitudinal design to address this gap by investigating what factors influence future involvement in misconduct and if these factors vary by type. Administrative data drawn from the records of 429 imprisoned men are examined to predict misconduct during a 1-year follow-up period. Findings reveal distinct differences by type and suggestions for targeted support and tailored interventions are made to help prevent future infractions within, and potentially after, incarceration.